Optical semiconductor element sealing sheet
By using a sealing resin layer containing an acrylic resin and a stripping sheet for optical semiconductor element sealing sheet, the problem of cumbersome and time-consuming liquid resin sealing method in the prior art is solved, and simple and efficient optical semiconductor element sealing is achieved.
Patent Information
- Application Number
- CN202180025748.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-25
- Filing Date
- 2021-03-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-03-12
AI Technical Summary
In the prior art, the method of sealing optical semiconductor components such as LEDs using liquid resins has problems such as complex processes, long time and poor processing.
The optical semiconductor element sealing sheet containing an acrylic resin and the release sheet attached to the sealing resin layer are sealed by simple steps and in a short time.
The sealing of optical semiconductor components with easy processing, simple process and short time is realized, and the sealing efficiency and quality are improved.
Smart Images

Figure CN115397870B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a sheet for sealing an optical semiconductor element, and more specifically, to a sheet for sealing one or more optical semiconductor elements arranged on a substrate. Background Art
[0002] It is known that a backlight used in a liquid crystal display device has a structure in which a plurality of LEDs are arranged on a substrate and the plurality of LEDs are sealed with a sealing resin. As a method for sealing the plurality of LEDs together with the sealing resin, there is known a method in which a liquid resin is poured into a region where the plurality of LEDs are arranged, the plurality of LEDs are buried, and then the liquid resin is cured by heat or ultraviolet irradiation (for example, see Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2017-66390 Summary of the invention
[0006] Problem that the invention aims to solve
[0007] However, the method of sealing optical semiconductor elements such as LEDs using liquid resin has the following problems: the process of uniformly applying the liquid resin and then curing the liquid resin by heating and irradiating it with ultraviolet rays is required, which is complicated and time-consuming. Furthermore, there are problems such as poor handling properties such as liquid dripping when applying the liquid resin and the liquid resin adhering to undesired areas.
[0008] The present invention has been conceived based on the above circumstances, and an object of the present invention is to provide a sheet for sealing an optical semiconductor element which is easy to handle and can seal an optical semiconductor element in a simple process in a short time.
[0009] Solutions for solving problems
[0010] The present inventors have conducted intensive research to achieve the above-mentioned object and have found that a sheet for sealing an optical semiconductor element comprising a sealing resin layer containing an acrylic resin and a release sheet attached to the sealing resin layer is easy to handle and can seal an optical semiconductor element in a simple process and in a short time. The present invention has been completed based on the above-mentioned findings.
[0011] That is, the present invention provides a sheet for sealing optical semiconductor elements, which is a sheet for sealing one or more optical semiconductor elements arranged on a substrate, and the sheet for sealing optical semiconductor elements comprises: a sealing resin layer for sealing the above-mentioned optical semiconductor elements, and a peeling sheet attached to the above-mentioned sealing resin layer, and the above-mentioned sealing resin layer contains an acrylic resin.
[0012] The optical semiconductor element sealing sheet includes a base layer, and the sealing resin layer may be sandwiched between the release sheet and the base layer.
[0013] It is preferred that the pencil hardness of the surface of the base material layer in the optical semiconductor element sealing sheet be 2H or more.
[0014] The total light transmittance of the optical semiconductor element sealing sheet in a state where the release sheet has been peeled off is preferably 85% or more.
[0015] The sealing resin layer may or may not contain a radiation-curable compound.
[0016] The present invention also provides an optical semiconductor device including a substrate, an optical semiconductor element disposed on the substrate, and the optical semiconductor element sealing sheet for sealing the optical semiconductor element.
[0017] The optical semiconductor device may be a backlight of a liquid crystal screen.
[0018] Furthermore, the present invention provides an image display device including the above-mentioned backlight and a display panel.
[0019] Furthermore, the optical semiconductor device may be a self-luminous display device.
[0020] Furthermore, the present invention provides an image display device including the self-luminous display device.
[0021] Effects of the Invention
[0022] The optical semiconductor element sealing sheet of the present invention is easy to handle and can seal an optical semiconductor element in a simple process in a short time. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a cross-sectional view of a sheet for sealing an optical semiconductor element according to one embodiment of the present invention.
[0024] Figure 2 This is a cross-sectional view of an optical semiconductor device using the sheet for sealing an optical semiconductor element according to one embodiment of the present invention.
[0025] Figure 3 (a) A plan view of a measurement sample used for evaluation of embeddability of an optical semiconductor element sealing sheet in an example and (b) a cross-sectional view of a cross section taken along a bb′ line in the plan view are shown.
[0026] Figure 4 (a) A plan view and (b) a cross-sectional view of a cross section taken along a bb′ line in the plan view of a measurement sample used for evaluation of embeddability of a liquid resin in a comparative example. DETAILED DESCRIPTION
[0027] [Sheet for sealing optical semiconductor elements]
[0028] The optical semiconductor element sealing sheet of the present invention comprises at least: a sealing resin layer for sealing the optical semiconductor element, and a peeling sheet attached to the sealing resin layer. It should be noted that, in this specification, the optical semiconductor element sealing sheet refers to a sheet for sealing one or more optical semiconductor element pairs arranged on a substrate. In addition, in this specification, "sealing the optical semiconductor element" means embedding at least a part of the optical semiconductor element into the sealing resin layer, including both direct sealing of the optical semiconductor element and indirect sealing (for example, sealing with the aid of other layers).
[0029] The optical semiconductor element sealing sheet of the present invention may also include a substrate layer in addition to the above-mentioned sealing resin layer and the above-mentioned release sheet. When the above-mentioned substrate layer is provided, the optical semiconductor element sealing sheet of the present invention includes a substrate layer on the surface of the above-mentioned sealing resin layer opposite to the surface to which the above-mentioned release sheet is attached. That is, the above-mentioned sealing resin layer is in a form sandwiched between the above-mentioned release sheet and the above-mentioned substrate layer. Hereinafter, one embodiment of the optical semiconductor element sealing sheet of the present invention is described.
[0030] Figure 1 Schematic cross-sectional view showing one embodiment of the optical semiconductor element sealing sheet of the present invention. Figure 1 As shown, the optical semiconductor element sealing sheet 1 can be used to seal one or more optical semiconductor elements arranged on a substrate, and includes a sealing resin layer 10 and a release sheet 20. The release sheet 20 is attached to one surface 10a of the sealing resin layer 10. In addition, a base material layer 30 is attached to the surface 10b of the sealing resin layer 10 that is opposite to the surface to which the release sheet 20 is attached. In other words, the optical semiconductor element sealing sheet 1 includes the base material layer 30, the sealing resin layer 10, and the release sheet 20 in this order.
[0031] The sealing resin layer is a resin layer that seals one or more optical semiconductor elements disposed on the substrate. The sealing resin layer may be a single layer or a laminate of the same or different sealing resin layers.
[0032] The sealing resin layer contains an acrylic resin. That is, the sealing resin layer is formed of a resin composition containing an acrylic resin. The sealing resin layer contains an acrylic resin, so that the optical semiconductor element has excellent embeddability and transparency. The acrylic resin is a polymer containing a structural unit derived from an acrylic monomer (a monomer component having a (meth)acryloyl group in the molecule) as a structural unit of the polymer. The acrylic resin can be used alone or in combination of two or more.
[0033] The acrylic resin is preferably a polymer containing the largest number of structural units derived from (meth)acrylate in terms of mass ratio. It should be noted that in this specification, "(meth)acrylic acid" means "acrylic acid" and / or "methacrylic acid" (either or both of "acrylic acid" and "methacrylic acid"), and the same applies to the others.
[0034] As the above-mentioned (meth)acrylate, for example, a hydrocarbon group-containing (meth)acrylate which may have an alkoxy group can be cited. As the hydrocarbon group-containing (meth)acrylate in the above-mentioned hydrocarbon group-containing (meth)acrylate which may have an alkoxy group, a (meth)acrylate alkyl ester having a straight-chain or branched aliphatic hydrocarbon group, a (meth)acrylate cycloalkyl ester having an alicyclic hydrocarbon group, and a (meth)acrylate aryl ester having an aromatic hydrocarbon group can be cited. The above-mentioned hydrocarbon group-containing (meth)acrylate which may have an alkoxy group may be used alone or in combination of two or more.
[0035] Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and tert-butyl (meth)acrylate. (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate (lauryl (meth)acrylate), tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, and the like.
[0036] As the alkyl (meth)acrylate, preferably, one having a linear or branched aliphatic hydrocarbon group having 1 to 20 carbon atoms (preferably 1 to 14, more preferably 2 to 10, and even more preferably 2 to 8) is used. When the carbon number is within the above range, the glass transition temperature of the acrylic resin can be easily adjusted, and the adhesiveness of the sealing resin layer can be easily made more appropriate.
[0037] Examples of the (meth)acrylate having an alicyclic hydrocarbon group include (meth)acrylates having a monocyclic aliphatic hydrocarbon ring such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate; (meth)acrylates having a dicyclic aliphatic hydrocarbon ring such as isobornyl (meth)acrylate; (meth)acrylates having a tricyclic aliphatic hydrocarbon ring such as dicyclopentyl (meth)acrylate, dicyclopentyloxyethyl (meth)acrylate, tricyclopentyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate. Among them, (meth)acrylates having a monocyclic aliphatic hydrocarbon ring are preferred, and cyclohexyl (meth)acrylate is more preferred.
[0038] Examples of the (meth)acrylate having an aromatic hydrocarbon group include phenyl (meth)acrylate and benzyl (meth)acrylate.
[0039] Examples of the hydrocarbon group-containing (meth)acrylate having an alkoxy group include those in which one or more hydrogen atoms in the hydrocarbon group of the above-mentioned hydrocarbon group-containing (meth)acrylate are replaced by alkoxy groups, and examples thereof include 2-methoxymethyl, 2-methoxyethyl, and 2-methoxybutyl (meth)acrylate.
[0040] The hydrocarbon group-containing (meth)acrylate which may have an alkoxy group preferably includes (meth)acrylic acid alkyl esters having a linear or branched aliphatic hydrocarbon group and (meth)acrylates having an alicyclic hydrocarbon group. In this case, the shear storage modulus of the sealing resin layer can be easily adjusted.
[0041] In order to properly exhibit the basic characteristics such as adhesiveness and adhesion to optical semiconductor elements brought by the hydrocarbon group-containing (meth)acrylate which may have an alkoxy group in the sealing resin layer, the proportion of the hydrocarbon group-containing (meth)acrylate which may have an alkoxy group in all the monomer components constituting the acrylic resin is preferably 40% by mass or more, more preferably 60% by mass or more relative to the total amount (100% by mass) of all the monomer components. In addition, from the viewpoint of copolymerization with other monomer components to obtain the effects of the other monomer components, the above proportion is preferably 95% by mass or less, more preferably 80% by mass or less.
[0042] The proportion of the (meth)acrylic acid alkyl ester having a linear or branched aliphatic hydrocarbon group in all the monomer components constituting the acrylic resin is preferably 30% by mass or more, more preferably 50% by mass or more, relative to the total amount (100% by mass) of all the monomer components. In addition, the above proportion is preferably 90% by mass or less, more preferably 70% by mass or less.
[0043] The ratio of the (meth)acrylate having an alicyclic hydrocarbon group in all monomer components constituting the acrylic resin is preferably 1% by mass or more, more preferably 5% by mass or more, relative to the total amount (100% by mass) of all monomer components. In addition, the ratio is preferably 30% by mass or less, more preferably 20% by mass or less.
[0044] For the purpose of improving cohesive force, heat resistance, etc., the acrylic resin may contain structural units derived from other monomer components copolymerizable with the hydrocarbon-containing (meth)acrylate that may have an alkoxy group. Examples of the other monomer components include polar group-containing monomers such as carboxyl-containing monomers, acid anhydride monomers, hydroxyl-containing monomers, glycidyl-containing monomers, sulfonic acid-containing monomers, phosphoric acid-containing monomers, and nitrogen-containing monomers. Each of the other monomer components may be used alone or in combination of two or more.
[0045] Examples of the carboxyl group-containing monomer include acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. Examples of the acid anhydride monomer include maleic anhydride, itaconic anhydride, etc.
[0046] Examples of the hydroxyl-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate.
[0047] Examples of the glycidyl group-containing monomer include glycidyl (meth)acrylate and methylglycidyl (meth)acrylate.
[0048] Examples of the sulfonic acid group-containing monomer include styrene sulfonic acid, allyl sulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid.
[0049] Examples of the phosphoric acid group-containing monomer include 2-hydroxyethyl acryloyl phosphate and the like.
[0050] Examples of the nitrogen atom-containing monomer include morpholine group-containing monomers such as (meth)acryloylmorpholine, cyano group-containing monomers such as (meth)acrylonitrile, and amide group-containing monomers such as (meth)acrylamide.
[0051] It is preferred that the polar group-containing monomer constituting the acrylic resin contains a hydroxyl-containing monomer. When the hydroxyl-containing monomer is contained, the acrylic resin and the sealing resin layer have excellent water resistance, and the optical semiconductor element sealing sheet is not prone to fogging even when used in a high humidity environment and has excellent whitening resistance.
[0052] As the above-mentioned hydroxyl-containing monomer, it is preferred to include 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate. 4-hydroxybutyl (meth)acrylate has low toxicity and particularly excellent water absorption, so the above-mentioned acrylic resin has excellent water resistance. However, 4-hydroxybutyl (meth)acrylate has high reactivity with isocyanate, and there is a concern that the gelation rate is fast when mixed with isocyanate compounds. Therefore, by using 4-hydroxybutyl (meth)acrylate and 2-hydroxyethyl (meth)acrylate in combination, the gelation rate can be appropriate when mixed with isocyanate compounds, and the water resistance of the above-mentioned acrylic resin is particularly excellent.
[0053] In order to appropriately exhibit the basic characteristics such as adhesiveness and adhesion to optical semiconductor elements brought by the hydrocarbon group-containing (meth)acrylate which may have an alkoxy group in the sealing resin layer, the proportion of the polar group-containing monomer in all monomer components constituting the acrylic resin is preferably 5 to 50% by mass, more preferably 10 to 40% by mass. In particular, from the viewpoint of making the sealing resin layer more water-resistant, the proportion of the hydroxyl-containing monomer is preferably within the above range.
[0054] The acrylic resin may contain a structural unit derived from a multifunctional monomer copolymerizable with the monomer components constituting the acrylic resin in order to form a crosslinked structure in its polymer skeleton. As the multifunctional monomer, for example, hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate and other multifunctional (meth)acrylates; epoxy (meth)acrylate (for example, poly(meth)acrylate glycidyl), polyester (meth)acrylate, urethane (meth)acrylate and other monomers having (meth)acryloyl groups and other reactive functional groups in the molecule. The multifunctional monomer may be used alone or in combination of two or more.
[0055] In order to properly exhibit the basic properties such as adhesion and close adhesion to optical semiconductor elements brought by the above-mentioned hydrocarbon-containing (meth)acrylate which may have an alkoxy group in the sealing resin layer, the proportion of the above-mentioned multifunctional monomer in all monomer components constituting the above-mentioned acrylic resin is preferably less than 40% by mass, more preferably less than 30% by mass.
[0056] The acrylic resin is preferably the base polymer (i.e., the polymer with the highest content) in the sealing resin layer. The content of the acrylic resin is not particularly limited, but is preferably 50% by mass or more (e.g., 50 to 100% by mass), more preferably 80% by mass or more (e.g., 80 to 100% by mass), and even more preferably 90% by mass or more (e.g., 90 to 100% by mass) relative to 100% by mass of the sealing resin layer. When the content is 50% by mass or more, the transparency of the optical semiconductor element sealing sheet is more excellent.
[0057] The acrylic resin is obtained by polymerizing the above-mentioned various monomer components. The polymerization method is not particularly limited, and examples thereof include solution polymerization, emulsion polymerization, bulk polymerization, polymerization by active energy ray irradiation (active energy ray polymerization), etc. In addition, the obtained acrylic resin may be a random copolymer, a block copolymer, a graft copolymer, etc.
[0058] Various common solvents can be used for the polymerization of the monomer components. Examples of the above-mentioned solvents include esters such as ethyl acetate and n-butyl acetate; aromatic hydrocarbons such as toluene and benzene; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; ketones such as methyl ethyl ketone and methyl isobutyl ketone, and other organic solvents. The above-mentioned solvents may be used alone or in combination of two or more.
[0059] The polymerization initiator, chain transfer agent, emulsifier, etc. used in the free radical polymerization of the monomer components are not particularly limited and can be appropriately selected for use. It should be noted that the weight average molecular weight of the acrylic resin can be controlled by the amount of the polymerization initiator and chain transfer agent and the reaction conditions, and the appropriate amount can be adjusted according to their types.
[0060] As the polymerization initiator used for polymerization of the monomer components, a thermal polymerization initiator, a photopolymerization initiator (photoinitiator), etc. may be used depending on the type of polymerization reaction. The above-mentioned polymerization initiators may be used alone or in combination of two or more.
[0061] The thermal polymerization initiator is not particularly limited, and examples thereof include azo polymerization initiators, peroxide polymerization initiators, redox polymerization initiators, etc. The amount of the thermal polymerization initiator used is preferably 1 part by mass or less, more preferably 0.005 to 1 part by mass, and further preferably 0.02 to 0.5 part by mass, relative to 100 parts by mass of the total amount of all monomer components constituting the acrylic resin.
[0062] Examples of the photopolymerization initiator include benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ketol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, thioxanthone photopolymerization initiators, acylphosphine oxide photopolymerization initiators, and titanocene photopolymerization initiators. Among them, acetophenone photopolymerization initiators are preferred.
[0063] Examples of the acetophenone-based photopolymerization initiator include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, 4-(tert-butyl)dichloroacetophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, and methoxyacetophenone.
[0064] The amount of the photopolymerization initiator used is preferably 0.005 to 1 part by mass, more preferably 0.01 to 0.7 part by mass, and still more preferably 0.18 to 0.5 part by mass relative to 100 parts by mass of the total amount of all monomer components constituting the acrylic resin. When the amount used is 0.005 part by mass or more (particularly 0.18 part by mass or more), it is easy to control the molecular weight of the acrylic resin to be small, and there is a tendency that the residual stress of the sealing resin layer becomes higher and the height difference absorption property becomes better.
[0065] The weight average molecular weight of the acrylic resin is not particularly limited, but is preferably 400,000 to 3,000,000, and more preferably 1,000,000 to 2,500,000. When the weight average molecular weight is within the above range, the shear storage modulus of the sealing resin layer can be easily adjusted. It should be noted that the weight average molecular weight refers to a value measured by gel permeation chromatography (GPC) and calculated by polystyrene conversion.
[0066] The resin composition forming the sealing resin layer may contain a crosslinking agent. For example, the acrylic resin can be crosslinked to further reduce the low molecular weight substances in the sealing resin layer. In addition, the weight average molecular weight of the acrylic resin can be increased. The crosslinking agent can be used alone or in combination of two or more.
[0067] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, melamine crosslinking agents, peroxide crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, amine crosslinking agents, silicone crosslinking agents, and silane crosslinking agents. Among the crosslinking agents, isocyanate crosslinking agents and epoxy crosslinking agents are preferred, and isocyanate crosslinking agents are more preferred, from the viewpoint of excellent adhesion to optical semiconductor elements and a small amount of impurity ions.
[0068] Examples of the isocyanate crosslinking agent (polyfunctional isocyanate compound) include lower aliphatic polyisocyanates such as 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate, and 1,6-hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated xylene diisocyanate; aromatic polyisocyanates such as 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate. In addition, examples of the isocyanate crosslinking agent include trimethylolpropane / toluene diisocyanate adducts, trimethylolpropane / hexamethylene diisocyanate adducts, and trimethylolpropane / xylylene diisocyanate adducts.
[0069] The content of the crosslinking agent is not particularly limited, but is preferably 5 parts by mass or less, more preferably 0.001 to 5 parts by mass, further preferably 0.005 to 2 parts by mass, and particularly preferably 0.02 to 0.7 parts by mass, based on 100 parts by mass of the base polymer.
[0070] The above-mentioned sealing resin layer can include other components other than the above-mentioned acrylic resin and the above-mentioned cross-linking agent within the scope of not damaging the effect of the present invention. As the above-mentioned other components, cross-linking accelerators, tackifying resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenols, etc.), oligomers, antioxidants, fillers (metal powders, organic fillers, inorganic fillers, etc.), colorants (pigments, dyes, etc.), antioxidants, plasticizers, softeners, surfactants, antistatic agents, surface lubricants, leveling agents, light stabilizers, ultraviolet absorbers, inhibitors, granular materials, foil-like materials, etc. can be cited. The above-mentioned other components can each be used only one, or two or more can be used.
[0071] The above-mentioned sealing resin layer may be a sealing resin layer containing a radiation-curable compound (radiation-curable sealing resin layer), or may be a sealing resin layer not containing a radiation-curable compound (non-radiation-curable sealing resin layer). As the above-mentioned radiation-curable compound, there may be mentioned radiation-polymerizable monomer components and oligomer components having functional groups such as radiation-polymerizable carbon-carbon double bonds. As specific examples of the above-mentioned radiation-curable sealing resin layer, for example, there may be mentioned an additive-type radiation-curable sealing resin layer, which contains the above-mentioned acrylic resin and radiation-polymerizable monomer components and / or oligomer components having functional groups such as radiation-polymerizable carbon-carbon double bonds; and an intrinsic radiation-curable adhesive, which contains an acrylic resin having functional groups such as radiation-polymerizable carbon-carbon double bonds in the polymer side chain, in the polymer main chain, and at the end of the polymer main chain.
[0072] Examples of the radiation polymerizable monomer component include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxy penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and 1,4-butanediol di(meth)acrylate.
[0073] Examples of the radiation-polymerizable oligomer component include various oligomers such as urethane-based, polyether-based, polyester-based, polycarbonate-based, and polybutadiene-based oligomers, and the molecular weight thereof is preferably about 100 to 30,000.
[0074] Examples of the radiation include electron beams, ultraviolet rays, α rays, β rays, γ rays, and X-rays. Among them, ultraviolet rays are preferred.
[0075] When the sealing resin layer is a multilayer layer, all the sealing resin layers may be radiation curable, all the sealing resin layers may not be radiation curable, or some of the sealing resin layers may be radiation curable and some of the sealing resin layers may not be radiation curable.
[0076] The sealing resin layer is formed of the acrylic resin or a monomer composition constituting the acrylic resin or a resin composition containing a prepolymer (partial polymer) thereof. The thickness of the sealing resin layer is not particularly limited, and is, for example, about 1 to 400 μm.
[0077] The shear storage modulus of the sealing resin layer at 23°C is preferably 6.0×10 4 ~9.0×10 5 Pa, more preferably 9.0×10 4 ~7.0×10 5 Pa, more preferably 1.1×10 5~5.0×10 5 Pa. The above shear storage modulus is 6.0×10 4 When the shear storage modulus is 9.0×10 5 Pa or less, the sealing resin layer has moderate softness and excellent embedding property of the optical semiconductor element. In particular, when multiple optical semiconductor elements are sealed at the same time, the sealing resin layer is required to simultaneously embed the concave-convex formed by the gap between the area where the optical semiconductor element is arranged and the optical semiconductor element. For the sealing resin layer having the shear storage modulus in the above range, the embedding property of the above concave-convex formed by multiple optical semiconductor elements is excellent. In addition, as a result, after sealing, the sealing resin layer has high adhesion with the optical semiconductor element and is not prone to blistering, so the brightness of the light emitted by the optical semiconductor element is not easy to decrease. It should be noted that the shear storage modulus at 23°C is a value measured by dynamic viscoelasticity measurement. For example, a sealing resin layer with a thickness of about 1.5 mm can be used as a measurement sample, and the measurement is performed in a shear mode, at a frequency of 1 Hz, in a temperature range of -70 to 200°C, and at a heating rate of 5°C / min.
[0078] The shear storage modulus of the sealing resin layer at 70°C is preferably 9.0×10 3 ~9.0×10 5 Pa, more preferably 1.0×10 4 ~7.0×10 5 Pa, more preferably 2.5×10 5 ~4.0×10 5 Pa. The above shear storage modulus is 9.0×10 3 Pa or more, the optical semiconductor element sealing performance is excellent, and the overflow of the sealing resin layer when the optical semiconductor element sealing sheet is attached can be further suppressed. 5 Pa or less, the sealing resin layer has moderate softness even in a relatively high temperature environment, and the optical semiconductor element sealing sheet is not easy to peel off when the optical semiconductor element is sealed. It should be noted that the shear storage modulus at 70°C is a value measured by dynamic viscoelasticity measurement. For example, a sealing resin layer with a thickness of about 1.5 mm can be used as a measurement sample, and the measurement can be performed in a shear mode, at a frequency of 1 Hz, in a temperature range of -70 to 200°C, and at a heating rate of 5°C / min.
[0079] The shear storage modulus refers to the shear storage modulus of each layer when the sealing resin layer consists of a plurality of layers. Some or all of the sealing resin layers may satisfy the shear storage modulus.
[0080] The haze value (initial haze value) of the sealing resin layer (in the case of a laminate of sealing resin layers, the laminate) is preferably 3.0% or less, more preferably 1.5% or less, and further preferably 1.2% or less. When the haze value is 3.0% or less, the transparency of the sealing resin layer and the optical semiconductor element sealing sheet is excellent. The haze value can be measured in accordance with JIS K7136.
[0081] The haze value of the sealing resin layer (the laminate in the case of a laminate of the sealing resin layer) after being stored for 120 hours in an environment of temperature 60°C and humidity 95% RH (haze value after storage in a high humidity environment) is preferably 4.0% or less, more preferably 3.0% or less, and further preferably 2.5% or less. When the haze value is 4.0% or less, the optical semiconductor element sealing sheet is not easy to fog even when used in a high humidity environment, and has excellent transparency. The haze value is measured in accordance with JIS K7136 for the sealing resin layer just after being taken out in an environment of temperature 23°C and humidity 50% RH after being stored in a high humidity environment.
[0082] The increase in the haze value after storage in a high humidity environment relative to the initial haze value of the sealing resin layer (the laminate in the case of a laminate of sealing resin layers) [haze value after storage in a high humidity environment - initial haze value] is preferably 3.0% or less, more preferably 1.5% or less, and further preferably 1.0% or less. When the increase in the haze value is 3.0% or less, the optical semiconductor element sealing sheet is not prone to fogging even when used in an environment where the humidity may be high due to temperature changes, and has excellent transparency.
[0083] (Peel-off Sheet)
[0084] The release sheet is an element for covering and protecting the surface of the sealing resin layer or an element that functions as a support before the optical semiconductor element sealing sheet is attached to a substrate on which the optical semiconductor element is disposed, and is peeled off from the sheet when the optical semiconductor element sealing sheet is used. The release sheet can be attached to both sides of the sealing resin layer, and can be attached to a single side of the sealing resin layer when a substrate layer is provided. In the case where the release sheet is provided on both sides of the sealing resin layer, for example, one release sheet is peeled off before the optical semiconductor element is sealed, and the exposed sealing resin layer is attached to the substrate in a manner that the optical semiconductor element is sealed, and the other release sheet is peeled off after sealing and used. In addition, in the case where the release sheet is provided on a single side of the sealing resin layer, for example, the release sheet is peeled off before the optical semiconductor element is sealed, and the exposed sealing resin layer is attached to the substrate in a manner that the optical semiconductor element is sealed and used.
[0085] When the above-mentioned release sheets are provided on both sides of the above-mentioned sealing resin layer, each optical semiconductor element sealing sheet may be in the form of a sheet having a release sheet, or the release sheet and the sealing resin layer may be in the form of a strip and the release sheet and the sealing resin layer are wound to form a roll. In addition, when the above-mentioned release sheets are provided on both sides of the above-mentioned sealing resin layer, the two release sheets may be the same or different.
[0086] Examples of the release sheet include polyethylene terephthalate (PET) films, polyethylene films, polypropylene films, plastic films surface-coated with a release agent such as a fluorine-based release agent or a long-chain alkyl acrylate-based release agent, and paper.
[0087] The thickness of the release sheet is, for example, 10 to 200 μm, preferably 15 to 150 μm, and more preferably 20 to 100 μm. When the thickness is 10 μm or more, the release sheet is less likely to be broken by cutting during processing. When the thickness is 200 μm or less, the release sheet is more easily peeled off from the sealing resin layer during use.
[0088] (Base material layer)
[0089] The substrate layer is an element that functions as a support in the optical semiconductor element sealing sheet, and is an element that functions as a protective layer for the optical semiconductor element and the sealing resin layer after the optical semiconductor element is sealed. As the substrate layer, for example, a plastic substrate (particularly a plastic film) is preferred. The substrate layer may be a single layer or a laminate of the same or different substrates.
[0090] As the resin constituting the above-mentioned plastic substrate, for example, there can be mentioned low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, ultra-low-density polyethylene, random copolymer polypropylene, block copolymer polypropylene, homopolymer polypropylene, polybutene, polymethylpentene, ethylene-vinyl acetate copolymer (EVA), ionomer, ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylate (random, alternating) copolymer, ethylene-butene copolymer, ethylene-hexene copolymer and other polyolefin resins; polyurethane; polyesters such as polyethylene terephthalate (PET), polyethylene naphthalate, polybutylene terephthalate (PBT); polycarbonate; polyimide; polyetheretherketone; polyetherimide; polyamides such as aramid and wholly aromatic polyamide; polyphenylene sulfide; fluororesin; polyvinyl chloride; polyvinylidene chloride; cellulose resin; silicone resin, etc. The above-mentioned resins may be used alone or in combination of two or more.
[0091] As the substrate layer, from the viewpoint of excellent transparency and scratch resistance, a plastic film is preferred, a polyester film or a polyolefin film is more preferred, and a polyethylene terephthalate film or a polypropylene film is particularly preferred.
[0092] For the surface of the substrate layer on the side with the sealing resin layer, for the purpose of improving the adhesion and retention of the sealing resin layer, for example, physical treatments such as corona discharge treatment, plasma treatment, sandblasting matte processing treatment, ozone exposure treatment, flame exposure treatment, high voltage electric shock exposure treatment, ionizing radiation treatment, chemical treatments such as chromic acid treatment, and surface treatments such as easy adhesion treatment using a coating agent (primer) can be applied. The surface treatment for improving adhesion is preferably applied to the entire surface of the substrate layer on the side of the sealing resin layer.
[0093] The pencil hardness of the surface of the substrate layer in the optical semiconductor element sealing sheet of the present invention is not particularly limited, and is preferably F or above (for example, F to 9H), more preferably H to 8H, and further preferably 2H to 7H. When the pencil hardness is F or above (especially 2H or above), after the sealing of the optical semiconductor element, the scratch resistance of the surface of the substrate layer is excellent, and it is less likely to hinder the transmission of light emitted by the optical semiconductor element. When the pencil hardness is 9H or less, the processability of the optical semiconductor element sealing sheet is excellent. The pencil hardness can be evaluated according to the method described in JIS K 5600-5-4.
[0094] From the viewpoint of excellent function as a support and surface scratch resistance, the thickness of the substrate layer is preferably 5 μm or more, more preferably 10 μm or more, and from the viewpoint of better transparency, the thickness of the substrate layer is preferably 300 μm or less, more preferably 200 μm or less.
[0095] The haze value (initial haze value) of the substrate layer is preferably 1.0% or less. When the haze value is 1.0% or less, the transparency of the optical semiconductor element encapsulating sheet is more excellent. The haze value can be measured in accordance with JIS K7136.
[0096] The total light transmittance of the optical semiconductor element sealing sheet of the present invention in the state where the above-mentioned release sheet is peeled off is preferably 85% or more, and more preferably 90% or more. When the above-mentioned total light transmittance is 85% or more, the transmittance of the light emitted by the optical semiconductor element is excellent. The upper limit of the above-mentioned total light transmittance is preferably 100%, and it can also be 99%. The above-mentioned total light transmittance is a value measured in the state where the above-mentioned release sheet is peeled off. When the two sides of the sealing resin layer are provided with release sheets, the measurement is carried out in the state where the two release sheets are peeled off. When only one side of the sealing resin layer is provided with a release sheet, the measurement is carried out in the state where the release sheet is peeled off. In addition, when the above-mentioned optical semiconductor element sealing sheet has a curable layer, the above-mentioned total light transmittance refers to the value in the state where the above-mentioned curable layer has been cured. This is because, for the optical semiconductor element sealing sheet, the transmittance of light in the use state of the final product such as the image display device described later is important. The above-mentioned total light transmittance can be measured in accordance with JIS K7361-1.
[0097] The optical semiconductor element sealing sheet of the present invention can be produced by forming the above-mentioned sealing resin layer on the release-treated surface of the above-mentioned release sheet, and can also be produced by further laminating the above-mentioned substrate layer or another release sheet on the surface of the above-mentioned sealing resin layer. In addition, the optical semiconductor element sealing sheet of the present invention can be produced by forming the above-mentioned sealing resin layer on the above-mentioned substrate layer, and further laminating the above-mentioned release sheet on the surface of the above-mentioned sealing resin layer. The above-mentioned sealing resin layer can be produced as follows: after the resin composition forming the sealing resin layer is coated on the release-treated surface of the release sheet or the substrate layer to form a resin composition layer, desolvation and curing based on heating, or curing based on active energy ray irradiation are performed to cure the resin composition layer. As the coating method of the resin composition, for example, roller coating, screen coating, gravure coating, etc. can be cited.
[0098] By using the optical semiconductor device sealing sheet of the present invention, a sealing resin layer is bonded to a substrate on which an optical semiconductor element is arranged, so that the optical semiconductor element is sealed by the sealing resin layer, thereby obtaining an optical semiconductor device. Specifically, first, a release sheet is peeled off from the optical semiconductor element sealing sheet of the present invention to expose the sealing resin layer. Then, in an optical component having a substrate and an optical semiconductor element (preferably a plurality of optical semiconductor elements) arranged on the above-mentioned substrate, the substrate surface on which the optical semiconductor element is arranged is bonded as the sealing resin layer surface of the optical semiconductor element sealing sheet of the present invention as the exposed surface. When the above-mentioned optical component has a plurality of optical semiconductor elements, the sealing resin layer is further arranged in a manner that fills the gaps between the plurality of optical semiconductor elements, so that the plurality of optical semiconductor elements are sealed together. Thereafter, the sealing resin layer can be cured by heating or irradiation with active energy rays as needed. In this way, the optical semiconductor element can be sealed by using the optical semiconductor device sealing sheet of the present invention. In addition, the optical semiconductor device sealing sheet of the present invention can be used to bond under reduced pressure or under pressure, thereby sealing the optical semiconductor element. Examples of such a method include the method disclosed in Japanese Patent Application Laid-Open No. 2016-29689 and Japanese Patent Application Laid-Open No. 6-97268.
[0099] [Optical semiconductor device]
[0100] The optical semiconductor device produced using the optical semiconductor element sealing sheet of the present invention comprises a substrate, an optical semiconductor element arranged on the substrate, and the optical semiconductor element sealing sheet of the present invention for sealing the optical semiconductor element.
[0101] Examples of the optical semiconductor element include light emitting diodes (LEDs) such as a blue light emitting diode, a green light emitting diode, a red light emitting diode, and an ultraviolet light emitting diode.
[0102] In the above-mentioned optical semiconductor device, the optical semiconductor element sealing sheet of the present invention preferably seals a plurality of optical semiconductor elements at a time because it has excellent followability to projections and recesses when the optical semiconductor element is a projection and the gaps between the plurality of optical semiconductor elements are recesses and has excellent embedding properties of the optical semiconductor element.
[0103] Figure 2 Show use Figure 1 One embodiment of an optical semiconductor device of the optical semiconductor element sealing sheet 1 shown. Figure 2The optical semiconductor device 2 shown includes: a substrate 21, a plurality of optical semiconductor elements 22 arranged on one surface of the substrate 21, and an optical semiconductor element sealing sheet 1' for sealing the optical semiconductor elements 22. The optical semiconductor element sealing sheet 1' is obtained by peeling off a release sheet 20 from the optical semiconductor element sealing sheet 1. The plurality of optical semiconductor elements 22 are sealed together by a sealing resin layer 10. The sealing resin layer 10 follows the concave-convex shape formed by the plurality of optical semiconductor elements 22 and is in close contact with the optical semiconductor elements 22 and the substrate 21, and embeds the optical semiconductor elements 22.
[0104] The above-mentioned optical semiconductor device is preferably a backlight of a liquid crystal screen, and is particularly preferably a backlight of the entire surface direct-down type. In addition, an image display device can be made by combining the above-mentioned backlight and a display panel. When the above-mentioned optical semiconductor device is a backlight of a liquid crystal screen, the optical semiconductor element is an LED element. For example, in the above-mentioned backlight, a metal wiring layer for transmitting a light-emitting control signal to each LED element is stacked on the above-mentioned substrate. Each LED element that emits light of various colors of red (R), green (G), and blue (B) is alternately arranged on the substrate of the display panel with the aid of a metal wiring layer. The metal wiring layer is formed of metals such as copper, which causes the light emission of each LED element to reduce the visual recognizability of the image. In addition, the light emitted by each LED element of each color of RGB is mixed and the contrast is reduced.
[0105] In addition, the above-mentioned optical semiconductor device is preferably a self-luminous display device. In addition, an image display device can be made by combining the above-mentioned self-luminous display device and a display panel as needed. When the above-mentioned optical semiconductor device is a self-luminous display device, the optical semiconductor element is an LED element. As the above-mentioned self-luminous display device, an organic electroluminescent (organic EL) display device and the like can be cited. For example, in the above-mentioned self-luminous display device, a metal wiring layer for transmitting a light control signal to each LED element is stacked on the above-mentioned substrate. Each LED element that emits light of various colors such as red (R), green (G), and blue (B) is alternately arranged on the substrate with the help of a metal wiring layer. The metal wiring layer is formed of metals such as copper, and the light emission degree of each LED element is adjusted to display various colors.
[0106] The optical semiconductor element sealing sheet of the present invention can be used in an optical semiconductor device that is used in a bent state, such as an optical semiconductor device having a bendable image display device (flexible display) (particularly a foldable image display device (foldable display)). Specifically, it can be used in a foldable backlight and a foldable self-luminous display device.
[0107] The optical semiconductor element sealing sheet of the present invention is excellent in embedding properties of an optical semiconductor element, and therefore can be preferably used in both the case where the optical semiconductor device is a mini LED display device and the case where the optical semiconductor device is a micro LED display device.
[0108] Example
[0109] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples at all.
[0110] Example 1
[0111] 67 parts by mass of butyl acrylate (BA), 14 parts by mass of cyclohexyl acrylate (CHA), 27 parts by mass of 4-hydroxybutyl acrylate (4HBA), 9 parts by mass of 2-hydroxyethyl acrylate (HEA), 0.05 parts by mass of 2,2-dimethoxy-1,2-diphenyl-1-one (trade name "omnirad 651", manufactured by IGM Resins Italia Srl), and 0.05 parts by mass of 1-hydroxycyclohexyl phenyl ketone (trade name "omnirad 184", manufactured by IGM Resins Italia Srl) were placed in a four-necked flask, and the mixture was exposed to ultraviolet rays in a nitrogen atmosphere to partially perform photopolymerization, thereby obtaining a partial polymer (monomer syrup) having a polymerization rate of 10%. To 100 parts by mass of the partial polymer, 0.1 parts by mass of an isocyanate compound (trade name "CORONATE L", manufactured by Tosoh Corporation, solid content 75% by mass) was added in terms of solid content, and these were uniformly mixed to prepare a photopolymerizable composition.
[0112] The photopolymerizable composition was applied to the release-treated surface of a release sheet (trade name "MRF38", manufactured by Mitsubishi Chemical Corporation, a polyethylene terephthalate film with a single surface subjected to release treatment, thickness 38 μm) to form a resin composition layer, and the release-treated surface of the release sheet was also attached to the resin composition layer. Next, a black light was used at an irradiation intensity of 5 mW / cm 2 The accumulated light intensity is 3600mJ / cm 2 , and polymerization was performed to form a sealing resin layer (thickness: 200 μm) of Example 1, thereby producing a sheet for sealing an optical semiconductor element of Example 1.
[0113] Example 2
[0114] A photopolymerizable composition was prepared in the same manner as in Example 1, and the sealing resin layer and optical semiconductor element sealing sheet of Example 2 were prepared using the photopolymerizable composition, except that the added amount of the isocyanate compound (trade name "CORONATE L", manufactured by Tosoh Corporation, solid content 75% by mass) was set to 0.05 parts by mass in terms of solid content.
[0115] Example 3
[0116] After the photopolymerizable composition prepared in Example 1 was applied to the release-treated surface of a release sheet (trade name "MRF38", manufactured by Mitsubishi Chemical Corporation, a polyethylene terephthalate film subjected to release treatment on one side, thickness 38 μm) to form a resin composition layer, the easy-adhesion-treated surface of a substrate film (trade name "Diafoil T912E75 (UE80-)", manufactured by Mitsubishi Chemical Corporation, a polyethylene terephthalate film subjected to easy-adhesion treatment on one side, thickness 75 μm, pencil hardness 2H) was attached to the resin composition layer. Next, a black light was used at an irradiation intensity of 5 mW / cm 2 The accumulated light intensity is 3600mJ / cm 2 , and polymerization was carried out to form a sealing resin layer (thickness: 200 μm) of Example 3, thereby producing a sheet for sealing an optical semiconductor element of Example 3.
[0117] Example 4
[0118] A sealing resin layer and an optical semiconductor element sealing sheet of Example 4 were prepared in the same manner as in Example 3 except that the photopolymerizable composition prepared in Example 2 was used.
[0119] Example 5
[0120] <Ultraviolet Curable Sealing Resin Layer>
[0121] 189.77 parts by mass of butyl acrylate (BA), 38.04 parts by mass of cyclohexyl acrylate (CHA), 85.93 parts by mass of 2-hydroxyethyl acrylate (HEA), 379.31 parts by mass of methyl ethyl ketone as a solvent, and 0.94 parts by mass of azobisisobutyronitrile were mixed to obtain a monomer composition. The obtained monomer composition was put into a polymerization experimental device equipped with a detachable lid, a separatory funnel, a thermometer, a nitrogen inlet tube, a Liebig condenser, a vacuum seal, a stirring rod, and a stirring blade on a 1L round-bottomed separable flask, and nitrogen replacement was performed at room temperature for 6 hours while stirring. Thereafter, polymerization was performed while stirring at 65°C for 4 hours and then at 75°C for 2 hours while flowing nitrogen to obtain a resin solution (prepolymer).
[0122] Next, the obtained resin solution was cooled to room temperature. Thereafter, 34.45 parts by mass of 2-isocyanatoethyl methacrylate (trade name "Karenz MOI", manufactured by Showa Denko K.K.) as a compound having a polymerizable carbon-carbon double bond was added to the above resin solution. 0.17 parts by mass of dibutyltin (IV) dilaurate (manufactured by FUJIFILM Wako Pure Chemical Corporation) was further added, and the mixture was stirred at 50° C. for 24 hours in an air atmosphere to obtain a base polymer.
[0123] 0.5 parts by mass of an isocyanate compound (trade name "CORONATE L", manufactured by Tosoh Corporation, solid content 75% by mass) and 1 part by mass of 2,2-dimethoxy-1,2-diphenyl-1-one (trade name "omnirad 651", manufactured by IGM Resins Italia Srl) were mixed with 100 parts by mass of the solid content of the obtained base polymer. Toluene was used as a diluent and the solid content was adjusted to 45% by mass to obtain a resin composition solution.
[0124] The resin composition solution is coated on the peeling surface of a peeling sheet (trade name "MRF38", manufactured by Mitsubishi Chemical Corporation, a single side of a polyethylene terephthalate film subjected to peeling treatment, thickness 38 μm), and dried at 120° C. for 3 minutes using a dryer to form a resin composition layer with a thickness of 150 μm. Next, the easy-bonding surface of a substrate film (trade name "Diafoil T912E75 (UE80-)", manufactured by Mitsubishi Chemical Corporation, a single side of a polyethylene terephthalate film subjected to easy-bonding treatment, thickness 75 μm, pencil hardness 2H) is attached to the resin composition layer. Thereafter, the resin composition layer is stabilized by keeping the entire sheet in a light-shielded state at 50° C. in a drying machine. Thereafter, the sheet is taken out from the drying machine, and the separator is peeled off from the resin composition layer. In this way, a UV-curable sealing resin layer is produced.
[0125] <Non-UV Curable Sealing Resin Layer>
[0126] 67 parts by mass of butyl acrylate (BA), 14 parts by mass of cyclohexyl acrylate (CHA), 27 parts by mass of 4-hydroxybutyl acrylate (4HBA), 9 parts by mass of 2-hydroxyethyl acrylate (HEA), 0.05 parts by mass of 2,2-dimethoxy-1,2-diphenyl-1-one (trade name "omnirad 651", manufactured by IGM Resins Italia Srl), and 0.05 parts by mass of 1-hydroxycyclohexyl phenyl ketone (trade name "omnirad 184", manufactured by IGM Resins Italia Srl) were placed in a four-necked flask, and the mixture was exposed to ultraviolet rays in a nitrogen atmosphere to partially perform photopolymerization, thereby obtaining a partial polymer (monomer syrup) having a polymerization rate of 10%. To 100 parts by mass of the partial polymer was added 0.05 parts by mass of an isocyanate compound (trade name "CORONATE L", manufactured by Tosoh Corporation, solid content 75% by mass) and then the mixture was uniformly mixed to prepare a photopolymerizable composition.
[0127] The photopolymerizable composition was applied to the release-treated surface of a release sheet (trade name "MRF38", manufactured by Mitsubishi Chemical Corporation, a polyethylene terephthalate film with a single surface subjected to release treatment, thickness 38 μm) to form a resin composition layer, and the release-treated surface of the release sheet was also attached to the resin composition layer. Next, a black light was used at an irradiation intensity of 5 mW / cm 2 The accumulated light intensity is 3600mJ / cm 2 , polymerization is carried out to produce a non-ultraviolet curable sealing resin layer (thickness: 50 μm).
[0128] <Sheet for sealing optical semiconductor elements>
[0129] A release sheet laminated on the non-ultraviolet curable sealing resin layer is peeled off, and the exposed surface of the non-ultraviolet curable sealing resin layer is overlapped with the exposed surface of the ultraviolet curable sealing resin layer, and the layers are bonded together using a hand roller. In this way, the sealing resin layer and optical semiconductor element sealing sheet of Example 5 having the structure of [base film / ultraviolet curable sealing resin layer / non-ultraviolet curable sealing resin layer / release sheet] are prepared.
[0130] <Evaluation>
[0131] The sealing resin layer and the optical semiconductor element sealing sheet obtained in the examples were evaluated as follows. The results are shown in the table. It should be noted that a liquid resin (trade name "LSP-3419", manufactured by Shin-Etsu Chemical Co., Ltd.) was used as Comparative Example 1, and a liquid resin (trade name "LSP-3412", manufactured by Shin-Etsu Chemical Co., Ltd.) was used as Comparative Example 2 for evaluation.
[0132] (1) Shear storage modulus
[0133] The sealing resin layers obtained in the examples are stacked to produce a stack of sealing resin layers with a thickness of about 1.5 mm as a measurement sample. The "Advanced Rheometric Expansion System (ARES)" manufactured by Rheometric Scientific is used to measure the above-mentioned measurement samples in a shear mode, at a frequency of 1 Hz, in a range of -70 to 200°C at a heating rate of 5°C / min, and the shear storage modulus at 23°C and 70°C is calculated. It should be noted that, for Example 5, the non-UV-curable sealing resin layer and the UV-curable sealing resin layer are measured separately. The above-mentioned UV-curable sealing resin layer is measured in the state before UV irradiation.
[0134] (2) Total light transmittance
[0135] From the optical semiconductor element sealing sheet obtained in the example, the release sheet (for Examples 1 and 2, any release sheet) is peeled off, and the exposed sealing resin layer is bonded to a glass plate (carrier glass, model "S-1111", manufactured by Matsunami Glass Industries, Ltd.). Then, for Examples 1 and 2, the other release liner is peeled off to prepare a measurement sample having a layer structure of [glass plate / sealing resin layer]. In addition, for Examples 3 and 4, a measurement sample having a layer structure of [glass plate / sealing resin layer / substrate layer] is prepared. In addition, for the comparative example, the liquid resin is flowed into a mold composed of a glass plate in such a way that the thickness after curing becomes 0.2 mm, and the resin is cured at 150°C for 4 hours to prepare a cured product, and the obtained laminate [glass plate / cured product] is used as a measurement sample. The total light transmittance of the above-mentioned measurement sample is measured using a haze meter (device name "HM-150", manufactured by Murakami Color Technology Research Institute Co., Ltd.). It should be noted that the total light transmittance shown in the table is the value of the measurement sample including the glass plate, so the total light transmittance of the sealing resin layer of the embodiment and the cured product of the comparative example is higher than the values shown in the table. It should be noted that for Example 5, after the measurement sample was prepared as in Examples 3 and 4, ultraviolet rays were irradiated from the substrate layer side to cure the ultraviolet curable sealing resin layer, and then the total light transmittance was measured. Ultraviolet irradiation was performed for 60 seconds using the trade name "UM810" (manufactured by Nitto Seiki Co., Ltd.).
[0136] (3) Haze value
[0137] For the measurement sample (laminated body [glass plate / cured product]) prepared to measure the total light transmittance (2) above, the total light transmittance and the diffuse transmittance were measured using a haze meter (device name "HM-150", manufactured by Murakami Color Research Institute Co., Ltd.). Then, the haze value of the measurement sample was calculated by the formula "diffuse transmittance / total light transmittance × 100" as the initial haze value. It should be noted that the haze values shown in the table are values of the measurement sample including the glass plate, so the haze values of the sealing resin layer of the embodiment and the cured product of the comparative example are lower than the values shown in the table.
[0138] (4) Presence of humidification turbidity (whitening resistance)
[0139] The release sheet (for Examples 1 and 2, any release sheet) is peeled off from the optical semiconductor element sealing sheet obtained in the examples, and the exposed sealing resin layer is bonded to a glass plate (carrier glass, trade name "MICRO SLIDEGLASS", model "S", manufactured by Matsunami Glass Industries, Ltd., thickness 1.3 mm, haze value 0.1%, water-polished). Then, for Examples 1 and 2, the other release liner is peeled off, and a PET film (trade name "A4100", manufactured by Toyobo Co., Ltd., thickness 100 μm, haze value 0.6%) is bonded to the exposed sealing resin layer. For Examples 3 to 5, the base film (PET film) is not peeled off and is kept as is. In this way, measurement samples of Examples 1 to 5 having the structure of [carrier glass / sealing resin layer / PET film] are prepared. In addition, for the comparative example, the liquid resin was flowed into a mold composed of glass plates in such a manner that the thickness after curing became 0.2 mm, and cured at 150°C for 4 hours to produce a cured product, and a measurement sample having the structure of [carrier glass / cured product] was produced. It should be noted that the measurement sample of the comparative example was not bonded with a PET film. Then, in the same manner as the determination of the initial haze value, the haze value (haze value after storage in a high humidity environment) of the measurement sample just after the measurement sample was stored at a temperature of 60°C and a humidity of 95% RH for 120 hours and then taken out at a temperature of 23°C and a humidity of 50% RH was measured. The haze before and after storage at a temperature of 60°C and a humidity of 95% RH was compared, and the case where the increase in the haze value calculated by [haze value after high humidity storage - initial haze value] was less than 1.0% (% point) was judged as ○ (no humidification turbidity, good whitening resistance), and the case where the increase in the haze value was 1.0% (% point) or more was judged as × (there was humidification turbidity, poor whitening resistance). It should be noted that the results are shown in the "whitening resistance" column of Table 1.
[0140] (4) Embeddability
[0141] <Preparation of simulation chip>
[0142] A dummy chip (size: 1 mm×1 mm×100 μm) serving as an optical semiconductor element was prepared as follows.
[0143] (Production of cutting discs)
[0144] In a reaction container equipped with a condenser, a nitrogen inlet pipe, a thermometer, and a stirring device, 88.8 parts by mass of 2-ethylhexyl acrylate (2EHA), 11.2 parts by mass of 2-hydroxyethyl acrylate (HEA), 0.2 parts by mass of benzoyl peroxide, and 65 parts by mass of toluene were added, and polymerization treatment was performed at 61° C. for 6 hours in a nitrogen stream to prepare an acrylic polymer A. The molar ratio of 2EHA to HEA was set to 100 mol:20 mol.
[0145] To the acrylic polymer A, 12 parts by mass (80 mol relative to 100 mol of HEA) of 2-methacryloyloxyethyl isocyanate (MOI) was added, and an addition reaction treatment was performed at 50° C. for 48 hours in an air stream to prepare an acrylic polymer A′.
[0146] Next, 0.75 parts by mass of a polyisocyanate compound (trade name "CORONATE L", manufactured by Tosoh Corporation) and 3 parts by mass of a photopolymerization initiator (trade name "omnirad 651", manufactured by IGM Resins Italia Srl) were added to 100 parts by mass of the acrylic polymer system A' to prepare an adhesive solution. The adhesive solution was applied to the silicone-treated surface of a PET release liner and heated for crosslinking at 120° C. for 2 minutes to form an adhesive layer with a thickness of 30 μm.
[0147] On the other hand, an olefin multilayer film (100 μm thick, embossed on the LLDPE layer side) was prepared by laminating a layer (80 μm thick) of a mixed resin of polypropylene and ethylene-propylene rubber and a layer (20 μm thick) of a linear low-density polyethylene (LLDPE). The non-embossed surface of the olefin multilayer film was then attached to the adhesive layer surface, and aged in an oven at 50° C. for 24 hours. Thereafter, an ultraviolet irradiation device (trade name “UM-810”, manufactured by Nitto Seiki Co., Ltd.) was used to irradiate the film at a cumulative light intensity of 300 mJ / cm 2 In this method, only the workpiece portion (wafer mounting area) is irradiated with ultraviolet light from the olefin-based multilayer film side to produce a dicing sheet.
[0148] (Production of Chip Attach Film)
[0149] 100 parts by mass of acrylic resin (trade name "SG-70L", manufactured by Nagase ChemteX Corporation), 79 parts by mass of epoxy resin (trade name "HP-400", manufactured by DIC Corporation), 93 parts by mass of phenolic resin (trade name "H-4", manufactured by Meiwa Chemical Industry Co., Ltd.), 189 parts by mass of spherical silica (trade name "SO-25R", manufactured by ADMATECHS CO., LTD.), and 0.6 parts by mass of curing catalyst (trade name "2PHZ", manufactured by Shikoku Chemical Industry Co., Ltd.) were dissolved in methyl ethyl ketone to prepare an adhesive composition solution having a solid content concentration of 20% by mass. Then, the adhesive composition solution was applied to a PET film, and the solvent was volatilized and cured by heating at 150°C for 2 minutes to prepare a die attach film having a thickness of 25 μm.
[0150] (Production of dicing sheets with die attach films)
[0151] The die attach film produced above, which had been punched out in advance into a size capable of mounting an 8-inch wafer, was bonded to the adhesive layer of the dicing film produced above using a hand roller.
[0152] (Silicon Wafer Preparation)
[0153] A back grinding tape (trade name "ELP UB-3083D", manufactured by Nitto Denko Corporation) was attached to one side of an 8-inch silicon mirror wafer, and the back side of the wafer was back ground. The back grinding was performed using a grinding device (trade name "DFG-8560", manufactured by DISCO Inc.) so that the thickness of the wafer after back grinding was 100 μm.
[0154] (Manufacturing of analog chips)
[0155] The wafer surface with the back grinding tape was bonded to the wafer mounting area of the die attach film provided on the adhesive layer of the dicing sheet using a hand roller while heating at 40°C. Then, a high pressure mercury lamp was used to heat the wafer at a cumulative light intensity of 300 mJ / cm 2 The back grinding tape is irradiated with ultraviolet light from the back grinding tape side, and then the back grinding tape is peeled off.
[0156] Next, a dicing ring for an 8-inch wafer was attached to the area of the dicing sheet where the die attach film was not mounted using a hand roller. Then, a dicing device (trade name "DFD-6450", manufactured by DISCO Inc.) was used to cut the wafer into a size of 1 mm × 1 mm, thereby obtaining a silicon chip (1 mm × 1 mm) with a die attach film.
[0157] Next, a measurement sample is prepared. Pick up each of the cut silicon chips with chip attaching films from the dicing sheet, and attach the chips to a single side of a 4-inch silicon mirror wafer by arranging the chip attaching films of the silicon chips with chip attaching films in a grid pattern, 4 chips vertically and 4 chips horizontally, for a total of 16 chips, so that the interval between the chip attaching films and the adjacent silicon chips with chip attaching films becomes 10 mm. The chip attaching is performed in a state where the silicon mirror wafer is placed on a hot plate heated to 100°C. Thereafter, the silicon mirror wafer is heated in an oven at a temperature of 150°C for 1 hour, thereby preparing the chip attaching film. Figure 3 As shown, the measurement sample 3 having a concavo-convex shape is formed by mounting a dummy chip 32 (1 mm×1 mm×100 μm) on a 4-inch silicon wafer 31 via a die attach film 33 (1 mm×1 mm×25 μm).
[0158] <Embeddability Evaluation>
[0159] The release sheet (for Examples 1 and 2, any release sheet) is peeled off from the sheet for sealing the optical semiconductor element obtained in the embodiment, and the exposed sealing resin layer is bonded to the concave-convex surface (the surface on which the simulation chip is arranged) of the above-mentioned measurement sample using a vacuum wafer bonding machine (trade name "MSA840VIII", manufactured by Nitto Denko Corporation) to seal the simulation chip. Specifically, first, an 8-inch silicon mirror wafer is placed on the wafer bonding table of the above-mentioned vacuum wafer bonding machine, and then a release sheet of a double-sided adhesive tape (trade name "NO.5000NS", manufactured by Nitto Denko Corporation) cut to a 4-inch wafer size is peeled off and bonded to the 8-inch silicon mirror wafer, and the other release sheet surface is pressed with a hand pressure roller, thereby bonding a 4-inch wafer size double-sided adhesive tape to the 8-inch silicon mirror wafer. Next, the other release sheet of the double-sided adhesive tape is peeled off, and the 4-inch silicon wafer surface of the measurement sample (a measurement sample with a concave-convex shape formed by mounting a simulated chip on a 4-inch silicon wafer with the aid of a chip mounting film) is bonded to the exposed adhesive surface. In this way, an 8-inch silicon mirror wafer, a double-sided adhesive tape, and a measurement sample are stacked in sequence on the wafer attachment table of a vacuum wafer bonding machine. On the other hand, the release sheet is peeled off from the optical semiconductor element sealing sheet, and an 8-inch cutting ring is bonded to the exposed sealing resin layer. Then, the cutting ring bonded to the sealing resin layer is brought into contact with the 8-inch silicon mirror wafer around the area where the measurement sample is placed, and then heating / decompression is applied and sealing is performed under the following conditions. It should be noted that for Example 5, after the above-mentioned heating / decompression, ultraviolet rays are irradiated from the substrate film side to cure the ultraviolet curable sealing resin layer and seal. Ultraviolet irradiation is performed for 60 seconds using the trade name "UM810" (manufactured by Nitto Seiki Co., Ltd.).
[0160] (Sealing conditions)
[0161] Workbench heating temperature: 70℃
[0162] Workbench type: CONTACT
[0163] Attachment method: VACUUM
[0164] Attachment gap (the distance between the analog chip and the sealing resin layer before sealing): 1.0mm
[0165] Attachment time: 5.0 seconds
[0166] Intermediate layer exhaust time: 10.0 seconds
[0167] Initial exhaust time: 0 seconds
[0168] Vacuum degree during attachment: 50Pa
[0169] On the other hand, in the comparative example, in the above-mentioned measurement sample, a bank is formed so as to surround the outer side of the simulated chip arranged in a grid shape, and the liquid resin of the comparative example is flowed into the bank to seal the simulated chip. Specifically, Figure 4 As shown, a glass plate 34 having a thickness of 1.3 mm was attached to the silicon wafer 31 of the measurement sample 3 via the die attach film 33 obtained above so as to surround the dummy chips 32 arranged in a grid shape, and the die attach film 33 was heated at 150°C for 1 hour to thermally cure the die attach film 33, thereby bonding to form a dam 35, and the measurement sample 3' was prepared. Then, liquid resin was poured into the above-mentioned dam so that the thickness of the cured resin layer became 200 μm, and then heated at 150°C for 4 hours to thermally cure the liquid resin, thereby sealing the dummy chip.
[0170] Then, for each of the prepared measurement samples, bubbles (voids) between the dummy chip and the sealing resin layer near the dummy chip were observed using a microscope, and the absence of bubbles of 10 μm or more was evaluated as ○, and the presence of bubbles of 10 μm or more was evaluated as ×.
[0171] [Table 1]
[0172] (Table 1)
[0173]
[0174] ※a) indicates the value of the UV-curable sealing resin layer, b) indicates the value of the non-UV-curable sealing resin layer
[0175] As shown in Table 1, the optical semiconductor element sealing sheet (Example) of the present invention has a high total light transmittance, excellent transparency, and excellent resistance to humidification turbidity (whitening resistance). In addition, when the optical semiconductor element sealing sheet of the present invention is used to seal a simulated chip simulating an optical semiconductor element, the embedding property of the simulated chip is excellent, and it is evaluated that the embedding property of the optical semiconductor element is excellent. Furthermore, when the optical semiconductor element sealing sheet of the Example is used for sealing, since no liquid resin is used, it is easy to handle. In addition, the molding operation of the liquid resin is not required, the operability is excellent, and the optical semiconductor element can be sealed in a simple process. In addition, when the optical semiconductor element sealing sheet of Examples 1 to 4 is used, a curing process is not required. In addition, when the optical semiconductor element sealing sheet of Example 5 is used, the curing time is short, which is 60 seconds, so the optical semiconductor element can be sealed in a simple process and in a short time. On the other hand, in the case of using liquid resin (comparative example), the embeddability of the simulated chip meets the standard, but in order to handle the liquid resin, care must be taken to prevent the liquid resin from adhering to the surroundings, which makes it difficult to handle. In addition, thermal curing of the sealing resin also requires 4 hours. Therefore, compared with the case of using a sheet for sealing optical semiconductor elements, sealing is complicated and takes time.
[0176] Description of Reference Numerals
[0177] 1,1' Optical semiconductor element sealing sheet
[0178] 10 Sealing resin layer
[0179] 20 Peel Sheet
[0180] 30 Base material layer
[0181] 2 Optical semiconductor devices
[0182] 21 substrate
[0183] 22 Optical semiconductor components
[0184] 3,3' Determination sample
[0185] 31 Silicon Wafer
[0186] 32 Analog Chip
[0187] 33 Chip Attach Film
[0188] 34 Glass Plate
[0189] 35 embankments
Claims
1. A sheet for sealing an optical semiconductor element, which is used to seal one or more optical semiconductor elements arranged on a substrate. The optical semiconductor element sealing sheet includes: a sealing resin layer for sealing the optical semiconductor element; and a release sheet attached to the sealing resin layer. The sealing resin layer contains an acrylic resin, The monomer components constituting the acrylic resin include a hydroxyl-containing monomer, wherein the hydroxyl-containing monomer includes 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate, and the proportion of the hydroxyl-containing monomer in all monomer components constituting the acrylic resin is 5 to 50% by mass. The shear storage modulus of the sealing resin layer at 23°C is 6.0×10 4 ~9.0×10 5 Pa. 2 . The optical semiconductor element sealing sheet according to claim 1 , comprising a base material layer, wherein the sealing resin layer is sandwiched between the release sheet and the base material layer.
3. The optical semiconductor element sealing sheet according to claim 2, wherein The pencil hardness of the surface of the substrate layer is 2H or more.
4. The optical semiconductor element sealing sheet according to any one of claims 1 to 3, wherein The total light transmittance in a state where the release sheet is peeled off is 85% or more. 5 . The optical semiconductor element sealing sheet according to claim 1 , which contains no radiation-curable compound. 6 . The optical semiconductor element sealing sheet according to claim 1 , comprising a radiation-curable compound. 7 . An optical semiconductor device comprising: a substrate, an optical semiconductor element disposed on the substrate, and the optical semiconductor element sealing sheet according to claim 1 for sealing the optical semiconductor element. The optical semiconductor device according to claim 7 , which is a backlight of a liquid crystal screen. 9 . An image display device comprising a display panel and the backlight according to claim 8 . 10 . The optical semiconductor device according to claim 7 , which is a self-luminous display device. 11 . An image display device comprising the self-luminous display device according to claim 10 .
Citation Information
Patent Citations
Sticking device for adhesive tape on wafer
JP1994097268A
Method of processing optical device wafer
JP2016029689A
Thermosetting silicone resin composition, and optical semiconductor device and semiconductor package using molded article thereof
JP2017066390A
Sheet-like sealing material, sealing sheet, electronic-device sealing body, and organic electroluminescent element
CN105849220A
Sheet for sealing optical semiconductor device
JP2009253223A